Obama in Syria: strategic confusion in a time of US retrenchment - Τσιτσόπουλος, Χαράλαμπος (Πανεπιστήμιο Πελοποννήσου, 2018)
This dissertation deals with former US President Barack Obama’s policy towards Syria, after the outbreak of the country’s rebellion in 2011. With reference to Syria Barack Obama is widely considered to have been a realist. By explicating Obama’s policies vis-à-vis four main critical junctures in the country’s civil war, the essay aims to show that President Obama’s Syria policies were not realist, locating this within the context of his general failure to formulate and subsequently pursue a clearly defined grand strategy towards the country. Rather, it is asserted, Obama’s Syria policies were the sum of ad hoc measures informed by generally pragmatic instincts, which should not be equated with realism. Having inherited a bitter legacy from his predecessor and facing a regional and global context in flux, Obama’s overarching guiding principle was to keep America away from further adventurism, focus on domestic priorities, while preparing for a pivot to Asia. It is borne in mind that the Syrian conflict presented the President with immense complexities and was extremely hard to navigate. Yet from a US vantage pointpoint, while Obama cannot be reproached for pursuing a more cautious approach than President Bush, he can certainly be charged with not pinpointing America’s regional interests in the context of the Syrian war and then pursuing a clear strategy to advance these interests.
Keywords: Ηνωμένες Πολιτείες Αμερικής--Εξωτερικές σχέσεις; Αραβική Άνοιξη; Ηνωμένες Πολιτείες Αμερικής--Εξωτερικές σχέσεις--Συρία; Αμερικανική εξωτερική πολιτική; Barack Obama; Ρεαλισμός; Αραβική Άνοιξη; Συρία